2021
DOI: 10.59284/jgpeman60
|View full text |Cite
|
Sign up to set email alerts
|

Access to pre-hospital care among patients visiting emergency department of a tertiary hospital in Nepal: A Mixed Methods pilot study

Abstract: Introduction: Pre-hospital care covers assistance and immediate care to injured and seriously ill patients at the scene and during transfer to health facilities. Pre-hospital care demands skills and preparedness. Medical emergencies involve use of a range of transports other than ambulances in Nepal. The current pilot study aimed to explore the access to pre-hospital care and factors associated with it from both users and providers’ perspective. Method: Cross sectional concurrent parallel mixed method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(13 reference statements)
1
0
1
Order By: Relevance
“…This finding was consistent with the study conducted in Mekele [ 20 ], which revealed that patients’ travel distance of more than 30 minutes was more likely to result in the utilization of ambulance services. But, it was contrary to the study conducted in Thailand [ 31 ], which indicated that ≤15km distance from the health center was more likely to lead to ambulance service usage. This disparity was, once again, explained by the fact that the majority of participants in this study were inter-facility referred patients, but also because patients from the urban area utilized other non-ambulance modes of transportation.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…This finding was consistent with the study conducted in Mekele [ 20 ], which revealed that patients’ travel distance of more than 30 minutes was more likely to result in the utilization of ambulance services. But, it was contrary to the study conducted in Thailand [ 31 ], which indicated that ≤15km distance from the health center was more likely to lead to ambulance service usage. This disparity was, once again, explained by the fact that the majority of participants in this study were inter-facility referred patients, but also because patients from the urban area utilized other non-ambulance modes of transportation.…”
Section: Discussioncontrasting
confidence: 83%
“…This meant that ambulance service use in pre-hospital emergency conditions was higher in the study area if compared to the findings of previous studies conducted in Mekele city [ 16 ] and the capital, Addis Ababa, of Ethiopia [ 14 , 15 ]. Similarly, previous studies in LMIC including the studies undertaken in Ghana [ 10 ], Pakistan [ 11 ], Nepal [ 31 ], and Lebanon [ 12 ] have reported a lower proportion of ambulance service utilization in emergency health situations.…”
Section: Discussionsupporting
confidence: 54%